2022
DOI: 10.1080/21681805.2022.2104367
|View full text |Cite
|
Sign up to set email alerts
|

Temperature profiles during ureteroscopy with thulium fiber laser and holmium:YAG laser: Findings from a pre-clinical study

Abstract: Objective: The aim of this study was to investigate temperature profiles in both the renal pelvis and parenchyma during Thulium Fiber Laser (TFL) and Holmium:yttrium-aluminium-garnet (Ho:YAG) laser activation in an ex-vivo porcine model. Methods: Three porcine kidneys with intact renal pelvis and proximal ureters were used in the study. A temperature sensor was inserted through a nephrostomy tube into the renal pelvis and a second sensor was inserted directly into the renal parenchyma. Temperatures were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…This study is not consistent with two cadaveric and one living porcine experiments that demonstrated similar increase in temperature using whether TFL or Ho:YAG at similar settings [39 ▪▪ ,40,41]. Increasing the laser fiber diameter was associated with a higher temperature at a similar power setting [39 ▪▪ ,42].…”
Section: Evidence Synthesiscontrasting
confidence: 90%
See 2 more Smart Citations
“…This study is not consistent with two cadaveric and one living porcine experiments that demonstrated similar increase in temperature using whether TFL or Ho:YAG at similar settings [39 ▪▪ ,40,41]. Increasing the laser fiber diameter was associated with a higher temperature at a similar power setting [39 ▪▪ ,42].…”
Section: Evidence Synthesiscontrasting
confidence: 90%
“…An in vitro study reported higher temperature with TFL at the same settings without difference in the required time to reach average or maximum intra-ureteral temperatures between any laser system at all power settings tested [38]. This study is not consistent with two cadaveric and one living porcine experiments that demonstrated similar increase in temperature using whether TFL or Ho:YAG at similar settings [39 ▪▪ ,40,41]. Increasing the laser fiber diameter was associated with a higher temperature at a similar power setting [39 ▪▪ ,42].…”
Section: Evidence Synthesismentioning
confidence: 60%
See 1 more Smart Citation
“…Concerns regarding intrarenal temperature with the use of HP have raised [35][36][37] and more studies are needed to find the limits to avoid the potential damage [38][39] especially when treating ureteral stones [40][41][42]. For this issue, temperature sensors have been proposed [43].…”
Section: Disadvantagesmentioning
confidence: 99%
“…[ 4 ] To this end, a small laser fiber should be selected, as this helps to maximize the irrigation flow available and keeps temperatures low. [ 5 ] The surgeon is required to perform instrumentation with additional care when the patient is awake. Unintentional contact between the activated laser and the ureteral wall causes unwanted discomfort.…”
Section: Surgical Techniquementioning
confidence: 99%